Intravascular Papillary Endothelial Hyperplasia of Buccal Mucosa Masquerading as Mucocele - A Case Report - Deepak Pandiar; Reshma Poothakulath Krishnan; Aklesha Behera; Pratibha Ramani (Indian Journal of Dental Research)
Introduction: Oral intravascular papillary endothelial hyperplasia (IPEH) is a rare entity with only 105 cases reported so far. Labial and buccal mucosa are the commonly affected sites. These sites are coincidently subjected to continuous minor trauma, which led the researchers to opine that IPEH could have a traumatic etiology with a further role of fibroblast growth factors. Clinical Presentation: We report a case of IPEH of right buccal mucosa in a 35 years old South Indian male who clinically presented as mucocele. Histopathologically, multiple lesions were found. Immunohistochemical and histochemical findings have also been presented. Discussion: The case is supported by a plausible mechanism involved in the pathogenesis. Thus, IPEH must be included in the clinical differential diagnosis of oral mucoceles and hemangioma. Take-away Lessons: Being a reactive lesion, it does not require extensive treatment. Clinicians and histopathologists must be aware of this uncommon yet benign condition for appropriate therapy.